2007
DOI: 10.1136/bjsm.2006.033548
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and determinants of lower extremity running injuries in long distance runners: a systematic review

Abstract: The purpose of this study was to present a systematic overview of published reports on the incidence and associated potential risk factors of lower extremity running injuries in long distance runners. An electronic database search was conducted using the PubMed–Medline database. Two observers independently assessed the quality of the studies and a best evidence synthesis was used to summarise the results. The incidence of lower extremity running injuries ranged from 19.4% to 79.3%. The predominant site of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

45
872
10
66

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,135 publications
(993 citation statements)
references
References 28 publications
(51 reference statements)
45
872
10
66
Order By: Relevance
“…Em estudos nacionais 9,12,13 houve uma variação entre 25% e 40% na incidência de lesões enquanto em estudos internacionais Van Gent et al 11 identificou essa variação entre 19,4% e 92,4% em lesões de membros inferiores. O presente estudo, cuja análise envolveu 88 corredores, verificou a incidência de 43,2%, no entanto não houve apenas lesões de membros inferiores e o questionamento sobre as mesmas era referente a todo tempo de corrida do praticante, não apenas nos últimos seis meses como em estudo de Hino et al 12 , logo, há um indicativo de correlação entre o tempo de prática com lesão.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Em estudos nacionais 9,12,13 houve uma variação entre 25% e 40% na incidência de lesões enquanto em estudos internacionais Van Gent et al 11 identificou essa variação entre 19,4% e 92,4% em lesões de membros inferiores. O presente estudo, cuja análise envolveu 88 corredores, verificou a incidência de 43,2%, no entanto não houve apenas lesões de membros inferiores e o questionamento sobre as mesmas era referente a todo tempo de corrida do praticante, não apenas nos últimos seis meses como em estudo de Hino et al 12 , logo, há um indicativo de correlação entre o tempo de prática com lesão.…”
Section: Discussionunclassified
“…Relacionado à incidência de lesões, observa-se uma variação entre 19,4% e 92,4% em membros inferiores, sendo o joelho a região mais acometida 11 . Hino et al 12 verificou que 1/3 do sexo masculino e ¼ do sexo feminino sofreram alguma lesão nos seis meses que antecederam o início das provas de corrida de rua.…”
Section: Introductionunclassified
“…There are various intrinsic and extrinsic factors that may contribute to the risks of developing running-related injuries, such as history of previous injuries, training errors, improper biomechanics, environmental factors, and footwear (Fredericson & Misra, 2007;Lopes, Hespanhol Junior, Yeung, & Costa, 2012;Van Gent, et al, 2007;Wen, 2007). The amount, frequency, and timing of impact forces are considered as the major contributing factors in injury (Chambon, Delattre, Gueguen, Berton, & Rao, 2014;Clarke, Frederick, & Cooper, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…With such a large number of people running, the risk and incidence of running-related injuries will likely continue. During a 12-month period of running, it has been reported that up to 90% of runners will suffer a running-related injury (Fields, Sykes, Walker, & Jackson, 2010;Satterthwaite, Larmer, Gardiner, & Norton, 1996;Van Gent, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite this, runners are also known to be highly susceptible to chronic injuries [2], with an incidence rate of around 70% over the course of one year [3]. A number of intrinsic and extrinsic risk factors have been associated with the aetiology of running injuries, such as mileage, previous injury, number of years of training, training characteristics, running mechanics, surface and footwear [4].…”
Section: Introductionmentioning
confidence: 99%